Protein hydrolysate from salmon frames: Production, characteristics and antioxidative activity. Issue 2 (15th November 2018) - Idowu, Anthony Temitope; Benjakul, Soottawat; Sinthusamran, Sittichoke; Sookchoo, Pornsatit; Kishimura, Hideki
Abstract: Protein hydrolysates from two forms of salmon frames named "chunk" and "mince" were produced and characterized. Both samples were subjected to hydrolysis using alcalase and papain at 1%–3% (w/w protein) for 0–240 min. Hydrolysate prepared with either protease at 3% for 180 min had the solid yield of 24.05%–26.39%. Hydrolysates contained 79.20%–82.01% proteins, 6.03%–6.34% fat, 9.81%–11.09% ash, and 4.02%–5.80% moisture. Amino acid profile showed that all hydrolysates had glutamic acid/glutamine (113.45–117.56 mg/g sample), glycine (77.86–86.18 mg/g sample), aspartic acid/asparagine (76.04–78.67 mg/g sample), lysine (61.97–65.99 mg/g sample), and leucine (54.30–57.31 mg/g sample) as the predominant amino acids. The size distributions determined by gel filtration chromatography varied, depending on proteases and the form of frame used for the hydrolysis. Different hydrolysates showed varying antioxidant capacities. Thus, protein hydrolysates from salmon frame could be used as a nutritive supplement in the protein deficient foods. Practical applications: Frames of salmon are by‐products from salmon fish processing industries. The frames contained the remaining meat, hence they can be used for the preparation of protein hydrolysates. Generally, hydrolysates from fish by‐products have been regarded as a promising food supplement, because they are rich in amino acids. Additionally, hydrolysates possess antioxidant activity, which is of health benefit. To produce the hydrolysate with less time consumption, the use of frame chunk instead of minced frame can be of better choice. Thus, frame of salmon, especially in chunk form, could be used as a raw material for production of protein hydrolysate using alcalase. The hydrolysate produced from salmon frame could serve as an alternative nutritive supplement to tackle the nutrition inadequacies in foods.